Integrasi Fintech Syariah dan Prinsip Maqashid Syariah dalam Transformasi Layanan Keuangan Islam di Indonesia: Integrating Islamic Fintech and Maqashid al-Shariah Principles in the Transformation of Islamic Financial Services in Indonesia - kartika marella vanni; Lisda Sabrina (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2026)
Purpose: To analyze the integration of Islamic financial technology (fintech) with the principles of Maqashid al-Shariah as a normative foundation for developing financial products that are both Sharia-compliant and socially beneficial amid the rapid growth of digital financial services in Indonesia. Design/Methodology/Approach: This study employs a conceptual and analytical approach by examining the development of Islamic fintech in Indonesia and evaluating its alignment with Maqashid al-Shariah principles, particularly in relation to Sharia compliance, contract transparency, profit-sharing mechanisms, and financial literacy. Research Findings: The study finds that although Islamic fintech offers significant opportunities to enhance financial inclusion, its implementation faces several challenges, including ensuring compliance with Islamic law, maintaining transparency in contracts, establishing fair profit-sharing mechanisms, and improving public financial literacy. The findings further indicate that strengthening regulatory frameworks, enhancing Sharia education, and promoting collaboration among regulators, industry practitioners, and Sharia scholars are essential to developing a sustainable and Sharia-compliant fintech ecosystem. Contribution/Originality/Novelty: This study contributes by providing a Maqashid al-Shariah-based perspective for evaluating and developing Islamic fintech. It highlights how the objectives of Sharia—namely the protection of religion, life, intellect, lineage, and wealth—can serve as a comprehensive framework for designing innovative digital financial services that balance technological advancement with ethical and social responsibility.